Comparison of porcine and human adipose tissue loading responses under dynamic compression and shear: A pilot study. (January 2021) - Sun, Zhaonan; Lee, Sang-Hyun; Gepner, Bronislaw D.; Rigby, Joshua; Hallman, Jason J.; Kerrigan, Jason R.
Abstract: Understanding the mechanical properties of human adipose tissue, and its influence on seat belt-pelvis interaction is beneficial for computational human body models that are developed for injury prediction in the vehicle crashworthiness simulations. While various studies have characterized adipose tissue, most of the studies used porcine adipose tissue as a surrogate, and none of the studies were performed at loading rates relevant for motor vehicle collisions. In this work, the mechanical response of human and porcine adipose tissue was studied. Two dynamic loading modes (compression and simple shear) were tested in adipose tissue extracted from the human abdomen and porcine back. An Ogden hyperelastic model was used to fit the loading response, and specific material parameters were obtained for each specimen. Two-sample t-tests were performed to compare the effective shear moduli and peak stresses from porcine and human samples. The material response of the human adipose tissue was consistent with previous studies. Porcine adipose tissue was found to be significantly stiffer than human adipose tissue under compression and shear loading. Also, when material model parameters were fit to only one loading mode, the predicted response in the other mode showed a poor fit.